2014
DOI: 10.3892/mco.2014.256
|View full text |Cite
|
Sign up to set email alerts
|

Erlotinib with pemetrexed/cisplatin for patients with EGFR wild-type lung adenocarcinoma with brain metastases

Abstract: Abstract. Erlotinib and pemetrexed have been approved for the second-line treatment of non-small cell lung cancer. Recent reports indicated that erlotinib and pemetrexed exerted synergistic effects against lung adenocarcinoma. The available treatment options for lung cancer with brain metastases (BM) are currently limited. In the present study, we investigated the efficacy of the combined administration of erlotinib and pemetrexed in 9 patients with epidermal growth factor receptor (EGFR) wild-type lung adenoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Zhang et al (49) reported that some patients with advanced NSCLC with wild-type EGFR could benefit from the combination therapy of EGFR-TKI and platinum-based drugs. The present results suggested that the combination effects of gefitinib and cisplatin in H1299 and A549 varied, despite both cells containing wild-type EGFR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al (49) reported that some patients with advanced NSCLC with wild-type EGFR could benefit from the combination therapy of EGFR-TKI and platinum-based drugs. The present results suggested that the combination effects of gefitinib and cisplatin in H1299 and A549 varied, despite both cells containing wild-type EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was speculated that wild-type EGFR could not be used as a single biomarker to predict the combined effect of cisplatin and gefitinib. Hierarchical analyses of most previous clinical trials are based on EGFR genotype, which may explain the contradictory conclusions from the literature (9,14,15,49). Moreover, the biological difference of tumors may cause this inconsistency.…”
Section: Discussionmentioning
confidence: 99%